Feasibility study on the implementation of mahalanobis taguchi system and time driven activity based costing in electronic industry - Mohd Yazid, Abu; Nik Nurharyantie, Nik Mohd Kamil; Sri Nur Areena, Mohd Zaini (Penerbit Universiti Malaysia Pahang, 2021)
Electrical and electronic industry is one of Malaysia’s leading industries which covers around 24.5% in manufacturing production sector. With a continuous innovation of the Industry, inductor component gets higher demand from customer and it is good if there is a study to convince that those factors are really significant to the production as well. Meanwhile, the current costing being used is difficult to access the complete activities required for each workstation and need separate analysis to measure the un-used capacity in term of resources and cost. The objective of this work is to clarify the relationship between Mahalanobis-Taguchi system (MTS) and time driven activity-based costing (TDABC) in the electronic industry. The data collection is focused on inductor component by consiedring the historical data in 2018. MTS is used as a method to optimize various parameters while TDABC is used to measure the un-used capacity by constructing the time equation and capacity cost rate. There are 7 parameters considered which are condition of wire, condition of winding, condition of epoxy, condition of core, condition of lead part, condition of marking and condition of soldering. As a result, MTS is successfully developed the normal and abnormal Mahalanobis distance (MD). In February, the normal MD is 0.9998 and the abnormal is 15.6538 with 2 significant parameters with signal to noise is 0.1244. In addition, there are 3 parameters consistently influenced along 10 months such as condition of core, condition of lead part and condition of soldering and 2 parameters are not consistently influenced such as condition of epoxy and condition marking. On the other hand, the total used and un-used capacity of time are 257124.02 minutes and 5217031.43 minutes respectively while the total of used and un-used of cost are MYR6,296,493.10 and MYR6214807.07 respectively. Eventually, this work concludes that both methods are a great tool and feasible to be implemented in the electronic industry.